Hak Konstitusi Warga Negara Indonesia yang Menjadi Tenaga Kerja di Luar Negeri - Bakri, Syaiful (Attractive : Innovative Education Journal, 2024)
The The purpose of writing this article is to find out the Constitutional Rights of Indonesian Citizens Who Become Workers Abroad, Indonesian Migrant Workers (Overseas Migrant Workers) are every citizen who is eligible to work abroad in employment for a certain period of time by receiving wages. The labors are protect by Law Number 39 Year 2004 on the placement and protection of Indonesian Migrant Workers (Overseas Migrant Workers) abroad. The formulation of the problem in this research is how the protection of Indonesian Migrant Workers’ according to Law Number 39 Year 2004 concerning the placement and protection of workers abroad and how the implementation of Law No. 39 of 2004 For Indonesian Migrant Workers. Type of research used is descriptive analytical, the method used in this research is approach legislation. A legislative approach is an approach that is undertaken by incorporating relevant laws and regulations pertaining to legal issues being addressed. Based on the description of the background and discussion of this research, it can be concluded that the protection of Indonesian Migrant Workers according to Law Number 39 Year 2004 concerning the placement and protection of workers abroad of pre-placement, during placement, post-placement. As well as supervision of the implementation and protection of Indonesian workers carried out with the objective of reporting job vacancy, compulsory report on employment in the company, and job training. The application of Indonesian Migrant Workers Law pursuant to Law Number 39 Year 2004 is intended to protect the basic rights of workers / laborers and ensure equal opportunity and treatment without discrimination on any basis to achieve workers' welfare and the government remains accountable The fate of Indonesian Migrant Workers and protection of Indonesian Migrant Workers and with the existence of Article 94 of Law Number 39 Year 2004 mandates to establish BNP2TKI as an institution assigned by the state to provide legal protection to Indonesian Migrant Workers. Keywords: Indonesian Migrant Workers, Protection, Implementation